Efektivitas Absorben Kimia pada Wet Scrubber untuk Menurunkan Emisi CO dan CO2 - Sevila Rizki Damayanti; Novirina Hendrasarie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Burning bricks can pollute the surrounding air because the smoke produced contains CO and CO2 emissions. This burning causes air pollution and a greenhouse effect (damage to the ozone layer) due to the emission of carbon monoxide gas. Air containing CO and CO2 emissions can be cleaned using the absorption method. The use of a wet scrubber and chemical absorbents that are alkaline in nature will help maximise the absorption process. The aim of this research is to test which absorbent among KOH, NaOH and H2O has the best performance in reducing CO and CO2 levels using a wet scrubber reactor design with pall ring media in the brick burning process. The independent variables used consist of variations in absorbent type, absorbent concentration and media height. The absorbents used are NaOH, KOH and H2O. The respective concentrations of NaOH and KOH absorbents used were 2N, 4N and 6N. The height of the pall ring media was varied to 20 cm and 40 cm. The highest percentage reduction of CO reached 97.9% and CO2 96.0% when using 6N KOH absorbent and 40 cm pall ring media.